Hubungan antara kemampuan listening dan ketrampilan pronunciation pada pembelajar bahasa inggris - Ramadhanti, Erlinda (Maliki Interdisciplinary Journal, 2026)
Listening ability and pronunciation skills are two main components in learning English as a foreign language that are interrelated and inseparable. Listening plays a role as a receptive skill that allows learners to recognize language sounds, word stress, intonation, and proper pronunciation patterns. Meanwhile, pronunciation is a productive skill that determines the clarity and success of oral communication. This article aims to explain the relationship between listening skills and pronunciation skills in English learners, as well as emphasize the role of listening as the basis for developing accurate pronunciation. The discussion shows that improving listening skills can increase learners' phonological sensitivity, thereby helping to reduce pronunciation errors caused by differences in the sound systems between English and the native language. Consistent exposure to correct pronunciation models through listening activities also helps learners imitate and produce English sounds more accurately. Thus, listening ability and pronunciation skills have a mutually supportive relationship and contribute directly to improving oral communication skills in English language learning.